THE STUDY OF LAW ON INVESTMENT LIBERALISATION POLICIES IN THE REGION OF ASEAN AND THE EFFECTS ON INDONESIA - Yanti, Delfi (Yustisia, 2017)
In order to realize a single ASEAN market through the free flow of investment in ASEAN, the ASEAN member states have agreed on the ASEAN Comprehensive Investment Agreement or known by the term ACIA signed in Cha-Am (Thailand) on February 26, 2009. The issue is how the rule of law against the liberalization of foreign investment in the ACIA Agreement and how its influence on Indonesia. This research method is a normative juridical research by using a qualitative data analysis technique. Based on the Article 1 (a) of ACIA related to the purpose of the establishment of ACIA the ACIA Agreement contains the legal concept of foreign investment: an investment regime that is "free and open" in ASEAN in order to achieve the ultimate goal of economic integration within the ASEAN Economic Community. This is done through progressive liberalization measures on investment regimes in the Member States of ASEAN. The concept of investment liberalization in the ASEAN region is also well supported by the principles of National Treatment (Article 5 of ACIA) and the principles of Most Favored Nation Treatment/MFN Treatment (Article 6, paragraph 1 of ACIA) in which these two principles are widely known as the principles of law in international economic law. While Indonesia itself has been also engaged in signing and ratifying the ACIA Agreement through Presidential Regulations No. 49 of 2011. This certainly provides a challenge and an opportunity to take advantage of this Agreement, as well as adjust the settings of Indonesian foreign investment (Law No. 25 of 2007) with the consent of the ACIA.Keywords: Implementation; Liberalization of Investment; ASEAN Region; Influence and Indonesia.